2019
DOI: 10.5194/acp-19-14455-2019
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl sulfide and its role in aerosol formation and growth in the Arctic summer – a modelling study

Abstract: Abstract. Atmospheric dimethyl sulfide, DMS(g), is a climatically important sulfur compound and is the main source of biogenic sulfate aerosol in the Arctic atmosphere. DMS(g) production and emission to the atmosphere increase during the summer due to the greater ice-free sea surface and higher biological activity. We implemented DMS(g) in the Environment and Climate Change Canada’s (ECCC) online air quality forecast model, GEM-MACH (Global Environmental Multiscale–Modelling Air quality and CHemistry), and com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 92 publications
1
22
0
Order By: Relevance
“…Ambient concentrations of MSA were generally higher at Utqiaġvik than Oliktok Point and are significantly different based on the paired t ‐test ( α = 0.05, p = 0.048). Ghahremaninezhad et al (2019) reported that a global environmental systems model focused on the North American Arctic and Arctic Ocean indicated that the higher concentrations of DMS were expected in the Bering Sea and Bering Strait region than in other regions of the Arctic Ocean. Galí et al (2019) found that the Bering Sea had some of the higher DMS fluxes along with the Iceland Basin and the Northern Atlantic Ocean.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ambient concentrations of MSA were generally higher at Utqiaġvik than Oliktok Point and are significantly different based on the paired t ‐test ( α = 0.05, p = 0.048). Ghahremaninezhad et al (2019) reported that a global environmental systems model focused on the North American Arctic and Arctic Ocean indicated that the higher concentrations of DMS were expected in the Bering Sea and Bering Strait region than in other regions of the Arctic Ocean. Galí et al (2019) found that the Bering Sea had some of the higher DMS fluxes along with the Iceland Basin and the Northern Atlantic Ocean.…”
Section: Resultsmentioning
confidence: 99%
“…Emissions of dimethyl sulfide (DMS) released by phytoplankton can be influential in these processes. Studies have shown that oxidation products of DMS can control the formation of ultrafine particles in the clean summertime atmosphere, which can then grow large enough to act as CCN (Abbatt et al, 2019; Ghahremaninezhad et al, 2019; Leaitch et al, 2013; Nilsson & Leck, 2002; Pandis et al, 1994; Park et al, 2017; Rempillo et al, 2011). DMS is oxidized in the atmosphere to form sulfate and methanesulfonic acid (MSA) (Hatakeyama et al, 1985; Leaitch et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The concurrent increase in biogenic sulfate aerosols and smallsized particles (3-10 and 10-100 nm, respectively) reported for the Arctic atmosphere in May (Park et al, 2017) is a prime example that biogenic DMS is a major contributor to NPF. A model study reported that DMS enhanced the mass of sulfate particles in the size range 50-100 nm in regions north of 70 • N (Ghahremaninezhad et al, 2019). During the bloom and post-bloom periods a decline in anthropogenic sources and an increase in oceanic DMS source strength resulted in the transition of major sulfate sources from Anth-SO 2− 4 to Bio-SO 2− 4 , which highlights the increasing importance of biogenic sulfur aerosols in the summer Arctic atmosphere.…”
Section: Factors Affecting Variations In the S Aerosol Concentration In The Arctic Atmospherementioning
confidence: 99%
“…In the clean Arctic atmosphere, DMS oxidation end-products (mostly, sulfuric and methanesulfonic acids) readily form new aerosol particles that scatter sunlight (Dawson et al, 2012;Leaitch et al, 2013;Hodshire et al, 2019;Veres et al, 2020;Brean et al, 2021). Moreover, DMS derivatives contribute to the condensational growth of aerosols into cloud condensation nuclei (CCN; Ghahremaninezhad et al, 2019), altering the balance between cloud shortwave forcing (increasing cloud albedo) and longwave forcing (increasing heat retention) (Andreae and Rosenfeld, 2008;Carslaw et al, 2013;Mahmood et al, 2019). In aerosol-depleted areas and over the pack ice, this radiative balance is particularly sensitive to local CCN sources (Mauritsen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%